2017
DOI: 10.1039/c6ta10772a
|View full text |Cite
|
Sign up to set email alerts
|

A smart switchable bioinspired copper foam responding to different pH droplets for reversible oil–water separation

Abstract: A novel pH-responsive smart device has been developed for continuous separation of oil/water mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…The absorption intensity of P = O groups becomes significantly weak after being cross-linked with Fe (III) ion, and -OH peak at 3328 cm −1 becomes a little stronger (Figure 2a,b green curve). After hydrophobic modification, the characteristic absorption peaks of HT at 1471 cm −1 (-CS-), 2848 cm −1 (-CH 2 -) and 2925 cm −1 (-CH 3 ) appear (Figure 2a,b blue curve) [43]. These results confirm the successful incorporation of the hydrophobic function HT on the surface of the sponge.…”
Section: Oil/water Separation Experimentssupporting
confidence: 61%
“…The absorption intensity of P = O groups becomes significantly weak after being cross-linked with Fe (III) ion, and -OH peak at 3328 cm −1 becomes a little stronger (Figure 2a,b green curve). After hydrophobic modification, the characteristic absorption peaks of HT at 1471 cm −1 (-CS-), 2848 cm −1 (-CH 2 -) and 2925 cm −1 (-CH 3 ) appear (Figure 2a,b blue curve) [43]. These results confirm the successful incorporation of the hydrophobic function HT on the surface of the sponge.…”
Section: Oil/water Separation Experimentssupporting
confidence: 61%
“…[158][159][160][161][162][163] For example, Wang and co-workers reported a pH-responsive smart surface that allows oil wetting underwater, repels water at pH 6.5, and blocks oil at pH 2.0. [160] The HS(CH 2 ) 9 CH 3 and HS(CH 2 ) 10 COOH mixed-thiol-modified mesh can also be used to bidirectionally separate oil-water mixtures.…”
Section: Ph-responsive Surfaces For Separationmentioning
confidence: 99%
“…The porous 3D network of the foam surface provides not only microscale roughness but also tunnels for liquid absorption or separation. Liu et al reported a smart copper foam for pH‐responsive reversible separation of oil/water mixtures. The copper foam was roughened first by immersion into an AgNO 3 solution, after which a rough layer of silver was deposited onto the smooth copper skeleton surface.…”
Section: Manipulation Of Liquid Wetting Behaviorsmentioning
confidence: 99%